(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to understand the effect of various non-genetic factors on udder health and the correlation of Body Condition Score (BCS) with milk composition traits of Rathi cows maintained at Livestock Research Station (LRS), College of Veterinary and Animal Science, PGIVER, RAJUVAS, Bikaner, Rajasthan. Milk samples from 50 Rathi cows were collected and analyzed for milk composition parameters and Somatic Cell count. BCS of each animal was measured. Data regarding parity and stage of lactation were collected from the record register maintained at farm. The parity reflected a significant (P<0.05) effect on SCC. The effect of stage of lactation revealed a non-significant (P>0.05) effect on the Log10 SCC. Except fat percent, all other constituents (i.e. protein, SNF, lactose, density and freezing pint) were positively correlated (P< 0.05) with BCS.